Formando professores a distância : estudo do livro base para o ensino de Língua Portuguesa no Curso Norma Superior - UEM (1ª turma) - Cazaroto, Cláudia (2007)
An increasing number of educational institutions exist that provide distance education (DE). This is due to rules and norms at all educational levels and to technological progress in information and communication (ICT) that significantly contribute towards DE teachinglearning process. However, printed didactic material is still extant and frequently is the dominant issue of the DE process. Current research comprises the teaching-learning process of the Portuguese Language at the Distance Education Teacher Training Course of the State University of Maringá (UEM), Maringá PR Brazil, for the 2001-2004 students. The theoretical and methodological issues contained in the language textbook are discussed (LT). The qualitative and interpretative research has been undertaken from the language interaction point of view with Pragmatics. Results show that, although LT alleges to be oriented by social interaction, nevertheless it fails under such a theory; in fact, it often jeopardizes its application since it alternates interactional periods with traditional ones. As a rule, the textbook, however, satisfies the methodological particularities of a DE course. In fact, distance interaction is undertaken since it has a self-explaining stance and utilizes interesting dialogue resources between teachers and students through bubble texts (BT). LT has had a great success in its attempt to promote relationship between theory and practice and helps the student to be active in the construction of his/her own learning. On the other hand, some contents are out of place and incorrect when the fact that the course is made for primary school teachers is taken into account. It may finally be said that that LT is extremely careless in its formal aspects which may impair its contents.